Keanekaragaman Amfibi di Air Terjun Kota Lubuklinggau, Sumatera Selatan - Dian Samitra; Zico Fakhrur Rozi (Biota, 2021)
Lubuklinggau has many natural location that supports life of amphibians. Temam and Sando waterfall area were part of them. This study aims to determine diversity amphibian in the Temam and Sando Waterfall, Lubuklinggau City. The study was conducted from June to July 2020. The collection data used Visual Encounter Survey (VES) techniques and time search. he data were analyzed using relative abundance, and indexes of diversity, evenness, similarity, and dominance. 11 species of amphibians belonging to 5 families were found during the study. Odorrana hosii was found mostly during the study. Amphibian diversity in the waterfall of Lubuklinggau City was categorized as low.